Virus-Specific Immune Response in HBeAg-Negative Chronic Hepatitis B: Relationship with Clinical Profile and HBsAg Serum Levels - Loggi, Elisabetta; Bihl, Florian K.; Cursaro, Carmela; Granieri, Camilla; Galli, Silvia; Brodosi, Lucia; Furlini, Giuliano; Bernardi, Mauro; Brander, Christian; Andreone, Pietro (PloS one, 2013)
The immune impairment characterizing chronic hepatitis B (cHBV) infection is thought to be the consequence of persistent exposure to viral antigens. However, the immune correlates of different clinical stages of cHBV and their relation with different levels of HBsAg have not been investigated. The aim of the present study was to evaluate the relationship between HBV-specific T cells response and the degree of in vivo HBV control and HBsAg serum levels in HBeAg-HBeAb+ cHBV. Peripheral blood mononuclear cells from 42 patients with different clinical profiles (treatment-suppressed, inactive carriers and active hepatitis) of cHBV, 6 patients with resolved HBV infection and 10 HBV-uninfected individuals were tested with overlapping peptides spanning the entire HBV proteome. The frequency and magnitude of HBV-specific T cell responses was assessed by IFNγ ELISPOT assay. Serum HBsAg was quantified with a chemiluminescent immunoassay. The total breadth and magnitude of HBV-specific T cell responses did not differ significantly between the four groups. However, inactive carriers targeted preferentially the core region. In untreated patients, the breadth of the anti-core specific T cell response was inversely correlated with serum HBsAg concentrations as well as HBV-DNA and ALT levels and was significantly different in patients with HBsAg levels either above or below 1000 IU/mL. The same inverse association between anti-core T cell response and HBsAg levels was found in treated patients. Different clinical outcomes of cHBV infection are associated with the magnitude, breadth and specificity of the HBV-specific T cell response. Especially, robust anti-core T cell responses were found in the presence of reduced HBsAg serum levels, suggesting that core-specific T cell responses can mediate a protective effect on HBV control.